A non-fullerene macromolecular acceptor material, a preparation method thereof and an organic solar cell

CN122878337APending Publication Date: 2026-10-09YUNNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610836045.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

[0010]本发明首次设计并合成了基于喹喔啉结构修饰的A-DA’D-A型非富勒烯巨分子受体材料,其具有良好的光吸收能力,合适的分子前线轨道能级,以及一定的空间位阻。该非富勒烯巨分子受体材料作为活性层第三组分应用于三元有机太阳能电池中,能有效提高三元器件的VOC,使得三元器件的PCE显著提升;并且其作为活性层第三组分应用于三元半透明有机太阳能电池中,除提高三元半透明器件的PCE外,还能够提高平均可见光透过率、显色指数等光学指标,最终大幅增强了半透明有机太阳能电池的光利用率,在半透明有机太阳能电池领域展现出广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878337A_ABST
    Figure CN122878337A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of organic solar cell materials and devices, and discloses a non-fullerene macromolecular acceptor material, a preparation method thereof and an organic solar cell. The non-fullerene macromolecular acceptor material has a structure shown in formula (I); wherein in formula (I), R1, R2, R3 and R4 are each independently selected from C1-C30 alkyl; A1 and A2 are each independently a group shown in formula (II); in formula (II), R5 and R6 are cyclically combined to form a group selected from a substituted or unsubstituted benzene ring, a substituted or unsubstituted naphthalene ring and a substituted or unsubstituted thiophene ring. The non-fullerene macromolecular acceptor material has good light absorption capacity, and when the non-fullerene macromolecular acceptor material is applied to a ternary organic solar cell as a third component of an active layer, the PCE of the ternary device can be effectively improved V OC , and the PCE of the ternary device is significantly improved. Formula (I) formula (II).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic solar cell materials and devices, specifically to a non-fullerene macromolecular acceptor material and its preparation method, and an organic solar cell. Background Technology

[0002] Organic solar cells (OSCs) possess significant advantages such as lightweight, flexibility, easily tunable absorption spectra, large-area fabrication capabilities, and low cost, demonstrating immense application potential in fields like wearable electronic devices and building-integrated photovoltaics (BIPV). The active layer material is crucial in determining the photoelectric conversion efficiency (PCE) of OSCs; currently, high-performance OSCs typically employ an active layer composed of polymer donors and non-fullerene acceptors.

[0003] Quinoxaline units possess weak electron deficiency and numerous modifiable sites. Their quinone resonance characteristics facilitate lowering the recombination energy of molecules, thereby promoting charge transport and reducing energy loss in devices. A-DA'DA type non-fullerene acceptor materials modified with quinoxaline structures have achieved PCE exceeding 20%, demonstrating broad development prospects. By rigidly linking quinoxaline-modified A-DA'DA type non-fullerene small molecule acceptors with a central A' unit, sterically hindered A-DA'DA type non-fullerene giant acceptors can be constructed. These giant acceptors effectively prevent excessive aggregation of acceptor molecules, improving solubility while also enhancing charge mobility. For example, by selecting benzotrithiophene as the linker and rigidly linking three A-DA'DA type small molecule acceptors with quinoxaline as the central A' unit, a cloverleaf-shaped giant acceptor T-Qx-15Cl was synthesized. T-Qx-15Cl has a large torsion angle of 40°, and its three-dimensional structure effectively prevents excessive aggregation of acceptor molecules, reduces non-radiative energy loss, and achieves a high open-circuit voltage of 0.93 V. V OC Ultimately, a PCE of 20.1% was achieved.

[0004] On the other hand, with the increasing demand for applications such as building-integrated photovoltaics, semi-transparent organic solar cell devices place higher demands on non-fullerene acceptor materials: an ideal non-fullerene acceptor should have suitable transmittance in the visible light region while maintaining strong absorption in the near-infrared region to achieve photoelectric conversion.

[0005] Therefore, how to develop A-DA'DA type non-fullerene macromolecular acceptor materials with both high efficiency and good translucency through precise design of the central core A' unit based on quinoxaline structure modification has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] The purpose of this invention is to provide an A-DA'DA type non-fullerene macromolecular acceptor material that combines high efficiency and excellent translucency.

[0007] To achieve the above objectives, the first aspect of the present invention provides an A-DA'DA type non-fullerene macromolecular acceptor material based on quinoxaline structure modification, the non-fullerene macromolecular acceptor material having the structure shown in formula (I): Formula (I); Formula (II); In formula (I), R1, R2, R3 and R4 are each independently selected from C1-C30 alkyl groups; A1 and A2 are each independently groups represented by formula (II); in formula (II), R5 and R6 together cyclize to form a benzene ring selected from substituted or unsubstituted, a naphthalene ring selected from substituted or unsubstituted, or a thiophene ring selected from substituted or unsubstituted. Furthermore, the substituents optionally present on R5 and R6 are each independently selected from at least one of halogens, C1-C3 alkyl groups, and C1-C3 alkoxy groups.

[0008] The second aspect of this invention provides a method for preparing the A-DA'DA type non-fullerene macromolecular acceptor material based on quinoxaline structure modification as described in the first aspect, the method comprising the following steps: under an inert atmosphere, (1) In the presence of a solvent, compound A and compound B undergo a first condensation reaction to obtain compound C; (2) In the presence of a solvent, compound C is subjected to a formylation reaction with N,N-dimethylformamide (DMF) and phosphorus oxychloride to obtain compound D; (3) In the presence of solvent and pyridine, compound D and compound E are subjected to a second condensation reaction to obtain the non-fullerene macromolecular acceptor material shown in formula (I); Compound A: Compound B: ; Compound E: ;Formula (I): ; In formula (I), compound A, compound B, and compound E, the definitions of R1, R2, R3, R4, R5, R6, A1, and A2 correspond to the definitions described in the first aspect.

[0009] A third aspect of the present invention provides an organic solar cell comprising an active layer containing a donor material, an acceptor material, and a third component; The third component is the A-DA'DA type non-fullerene macromolecular acceptor material described in the first aspect.

[0010] This invention presents the first design and synthesis of an A-DA'DA type non-fullerene giant acceptor material based on quinoxaline structure modification. This material exhibits excellent light absorption, suitable molecular frontier orbital energy levels, and certain steric hindrance. When used as the third component of the active layer in ternary organic solar cells, this non-fullerene giant acceptor material can effectively improve the performance of ternary devices. V OC This significantly improves the PCE of ternary devices; and as the third component of the active layer, its application in ternary semi-transparent organic solar cells not only improves the PCE of ternary semi-transparent devices, but also improves optical indicators such as average visible light transmittance and color rendering index, ultimately greatly enhancing the light utilization of semi-transparent organic solar cells, showing broad application prospects in the field of semi-transparent organic solar cells. Attached Figure Description

[0011] Figure 1 This is the 1H NMR spectrum of compound 4 prepared in Example 1 of this invention.

[0012] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of compound 5 prepared in Example 1 of this invention.

[0013] Figure 3 This is the 1H NMR spectrum of the non-fullerene macromolecular acceptor material 3QX-IC prepared in Example 1 of this invention.

[0014] Figure 4 The UV-Vis absorption spectra of the non-fullerene macromolecular acceptor material 3QX-IC, the classical non-fullerene acceptor material BTP-eC9, and the classical donor material D18 prepared in Example 1 of this invention are shown.

[0015] Figure 5 The cyclic voltammetry curve of the non-fullerene macromolecular acceptor material 3QX-IC prepared in Example 1 of this invention is shown.

[0016] Figure 6 The diagram shows the energy level arrangement of the non-fullerene macromolecular acceptor material 3QX-IC, the classical non-fullerene acceptor material BTP-eC9, and the classical donor material D18 prepared in Example 1 of this invention.

[0017] Figure 7 The optimal geometric configurations calculated by DFT theory for the non-fullerene macromolecular acceptor material 3QX-IC and the classical non-fullerene acceptor material BTP-eC9 prepared in Example 1 of this invention.

[0018] Figure 8This is a current-voltage curve of different organic solar cells prepared in Test Example 2 of the present invention.

[0019] Figure 9 The graph shows the external quantum efficiency curves of different organic solar cells prepared in Test Example 2 of this invention.

[0020] Figure 10 This is the device structure of the semi-transparent organic solar cell prepared in Test Example 3 of the present invention.

[0021] Figure 11 The current-voltage curves are for different semi-transparent organic solar cells prepared in Test Example 3 of the present invention.

[0022] Figure 12 This is a transmittance curve of different semi-transparent organic solar cells prepared in Test Example 3 of the present invention.

[0023] Figure 13 The images show the visual effects of different semi-transparent organic solar cells prepared in Test Example 3 of this invention.

[0024] Figure 14 This is a CIE coordinate diagram of different semi-transparent organic solar cells prepared in Test Example 3 of the present invention. Detailed Implementation

[0025] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0026] In this invention, unless otherwise stated, the terminology is interpreted as follows: In this invention, the dashed lines (┄) in each structure represent the positions of group bonds.

[0027] "Halogen" includes any one or more of fluorine, chlorine, bromine, and iodine.

[0028] "C1-C30 alkyl groups" refers to alkyl groups with a total number of carbon atoms of 1-30, including straight-chain alkyl groups and branched alkyl groups with a total number of carbon atoms of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30. Examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, cyclopropyl, methylcyclopropyl, ethylcyclopropyl, cyclopentyl, methylcyclopentyl, and cyclohexyl. Similar interpretations exist for "C1-C3 alkyl groups" and "C6-C30 alkyl groups," and will not be elaborated upon here.

[0029] R5 and R6 cyclize together to form a benzene ring, a naphthalene ring, or a thiophene ring selected from substituted or unsubstituted benzene rings, substituted or unsubstituted naphthalene rings, or substituted or unsubstituted thiophene rings. This indicates that R5 and R6 form a cyclopentane ring with the group shown in formula (II), and that R5 and R6 cyclize together to form at least one ring structure selected from benzene rings, naphthalene rings, and thiophene rings. For example, it could be... , , , Furthermore, any position on the benzene ring, naphthalene ring, or thiophene ring that can be substituted can be substituted.

[0030] A substituted or unsubstituted benzene ring means that any substituted position on the benzene ring can be replaced by the corresponding group defined herein. Substituted or unsubstituted thiophene rings, substituted or unsubstituted naphthalene rings, etc., are given similar definitions below, and will not be repeated here.

[0031] As previously stated, the first aspect of this invention provides an A-DA'DA type non-fullerene macromolecular acceptor material based on quinoxaline structure modification, the non-fullerene macromolecular acceptor material having the structure shown in formula (I): Formula (I); Formula (II); In formula (I), R1, R2, R3 and R4 are each independently selected from C1-C30 alkyl groups; A1 and A2 are each independently groups represented by formula (II); in formula (II), R5 and R6 together cyclize to form a benzene ring selected from substituted or unsubstituted, a naphthalene ring selected from substituted or unsubstituted, or a thiophene ring selected from substituted or unsubstituted. Furthermore, the substituents optionally present on R5 and R6 are each independently selected from at least one of halogens, C1-C3 alkyl groups, and C1-C3 alkoxy groups.

[0032] Preferably, in formula (I), R1, R2, R3 and R4 are each independently selected from C6-C30 alkyl groups.

[0033] More preferably, R1, R2, R3, and R4 are each independently selected from one of the following groups: .

[0034] According to a preferred embodiment, in formula (I), A1 and A2 are each independently selected from one of the following groups: , , , ; Optionally, A1 and A2 may further contain at least one substituent selected from halogens, C1-C3 alkyl groups, and C1-C3 alkoxy groups.

[0035] According to another preferred embodiment, in formula (I), A1 and A2 are each independently selected from one of the following groups: .

[0036] According to a particularly preferred embodiment, the non-fullerene macromolecular acceptor material is selected from one of the following structures: .

[0037] More preferably, C8H 17 - is octylene; C 11 H 23 - is n-undecyl; C6H 13 - is hexyl. The inventors discovered that, under this preferred condition, the non-fullerene macromolecular acceptor material can better improve the photoelectric conversion efficiency and visible light transmittance of ternary devices.

[0038] To achieve a higher product yield, as previously described, a second aspect of the present invention provides a method for preparing the A-DA'DA type non-fullerene macromolecular acceptor material based on quinoxaline structure modification as described in the first aspect. This method includes the following steps: under an inert atmosphere... (1) In the presence of a solvent, compound A and compound B undergo a first condensation reaction to obtain compound C; (2) In the presence of a solvent, compound C is subjected to a formylation reaction with N,N-dimethylformamide (DMF) and phosphorus oxychloride to obtain compound D; (3) In the presence of solvent and pyridine, compound D and compound E are subjected to a second condensation reaction to obtain the non-fullerene macromolecular acceptor material shown in formula (I); Compound A: Compound B: ; Compound E: ;Formula (I): ; In formula (I), compound A, compound B, and compound E, the definitions of R1, R2, R3, R4, R5, R6, A1, and A2 correspond to the definitions described in the first aspect. Further details will not be repeated here, and those skilled in the art should not construe this as a limitation of the present invention.

[0039] According to a preferred embodiment, in step (1), the molar ratio of compound A to compound B is 3-6:1, preferably 5-6:1.

[0040] In some embodiments, in step (1), the solvent is a mixed solvent of chlorobenzene and acetic acid, and the volume ratio of chlorobenzene and acetic acid is 0.5-2:1, preferably 1:1; Preferably, in step (1), the amount of solvent used is 30-40 mL relative to 1 mmol of compound A.

[0041] In a preferred embodiment, in step (1), the conditions for the first condensation reaction include: a reaction temperature of 80-140°C, preferably 130°C, and a reaction time of 10-15 hours, preferably 12 hours.

[0042] In a preferred embodiment, in step (2), the amount of N,N-dimethylformamide used is 35-45 mL relative to 1 mmol of compound C, and the amount of phosphorus oxychloride used is 11-13 mL.

[0043] Preferably, in step (2), the solvent is 1,2-dichloroethane; the amount of the solvent used is 500-1000 mL relative to 1 mmol of compound C.

[0044] Preferably, in step (2), the specific operation of the formylation reaction includes: performing a first reaction with N,N-dimethylformamide and phosphorus oxychloride, and then adding a 1,2-dichloroethane solution containing compound C to perform a second reaction; to obtain compound D.

[0045] In a preferred embodiment, the conditions for the first reaction include: a temperature of 0-10 ℃ and a time of 1-3 hours; the conditions for the second reaction include: a temperature of 70-90 ℃ and a time of 10-15 hours.

[0046] Preferably, in step (3), the molar ratio of compound D to compound E is 1:16-18.

[0047] Preferably, in step (3), the solvent is chloroform, and the amount of chloroform used is 800-1600 mL relative to 1 mmol of compound D; the amount of pyridine used is 80-160 mL.

[0048] Preferably, the inert atmosphere is selected from at least one of nitrogen, helium, and argon.

[0049] In a preferred embodiment, the conditions for the second condensation reaction include: a reaction temperature of 60-70 °C and a reaction time of 10-15 hours.

[0050] The present invention provides a preferred method for preparing compound A, wherein compound A is prepared by means of the following steps: under the protection of an inert atmosphere, the compound represented by formula (III) is reduced with lithium aluminum hydride in a tetrahydrofuran solvent to obtain compound A; Formula (III); The definitions of R1, R2, R3, and R4 in equation (III) are the same as those described in the first aspect.

[0051] Preferably, the molar ratio of the compound shown in formula (III) to lithium aluminum hydride is 1:19-21.

[0052] Preferably, the conditions for the reduction reaction include: a temperature of 70-80 °C and a time of 5-7 hours.

[0053] In a preferred embodiment, the amount of tetrahydrofuran used is 40-60 mL relative to 1 mmol of the compound represented by formula (III).

[0054] The aforementioned preparation method of the present invention may also involve various post-processing operations known in the art, such as extraction, washing, filtration, column chromatography, recrystallization, etc. The present invention does not have any particular limitations in this regard, and those skilled in the art should not understand it as a limitation of the present invention.

[0055] The raw materials involved in the aforementioned method for preparing non-fullerene macromolecular acceptor materials described in this invention can be synthesized according to their structural formulas using organic synthesis methods within the art, or they can be commercially available. The following text of this invention provides exemplary methods for preparing a few raw materials, which should not be construed as limiting the invention by those skilled in the art.

[0056] As mentioned above, a third aspect of the present invention provides an organic solar cell comprising an active layer containing a donor material, an acceptor material, and a third component; The third component is the A-DA'DA type non-fullerene macromolecular acceptor material described in the first aspect.

[0057] Preferably, the organic solar cell comprises an anode, a hole transport layer, an active layer, an electron transport layer, and a cathode, which are stacked sequentially.

[0058] Preferably, the organic solar cell further includes an anti-reflective layer.

[0059] In a preferred embodiment, the mass ratio of the donor material to the acceptor material is 1:1-1.5. For example, it can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, or 1:1.5; preferably 1:1.2.

[0060] Preferably, the donor material is D18; the acceptor material is BTP-eC9.

[0061] In this invention, the CAS number of the donor material D18 is 2433725-54-1, and the CAS number of the acceptor material BTP-eC9 is 2598965-39-8.

[0062] Preferably, the third component accounts for 5-30 wt% of the total mass of the receptor material and the third component, and more preferably 10 wt%.

[0063] The present invention also provides a method for preparing the organic solar cell described in the third aspect, characterized in that the method comprises the following steps: (a) A hole transport layer is formed on the anode substrate using a spin coating method; (b) Spin-coating an active layer solution containing the non-fullerene acceptor material described in the first aspect onto the hole transport layer, and then annealing to form an active layer; (c) An electron transport layer is formed on the active layer using a spin coating method; (d) A cathode is deposited on the electron transport layer using a vacuum thermal evaporation method to obtain the organic solar cell.

[0064] Preferably, in step (b), the solvent of the active layer solution is a mixed solution of DIB and chloroform, and the concentration of DIB is 5 mg / mL. -1 .

[0065] Preferably, the total concentration of donor and acceptor materials in the active layer solution is 10-20 mg / mL. -1 11 mg / mL is preferred. -1 ; Preferably, the spin coating speed of the active layer solution is 2000-3000 rpm, and more preferably 2500 rpm.

[0066] Preferably, in step (b), the annealing temperature is 90-110 °C, more preferably 100 °C, and the time is 5-15 minutes, more preferably 10 minutes.

[0067] In a preferred embodiment, in step (a), the spin-coated hole transport layer solution is a poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) solution.

[0068] Preferably, in step (c), the spin-coated electron transport layer solution is PDIN (structural formula: (CAS No. 117901-97-0) Methanol solution; concentration 1-3 mg / mL -1 .

[0069] Preferably, the cathode is a copper electrode and / or a silver electrode; the thickness of the cathode is 5-100 nm. More preferably, the cathode is a Cu-Ag composite electrode composed of Cu with a thickness of 3 nm and Ag with a thickness of 5 nm.

[0070] Preferably, the method further includes depositing an anti-reflection layer on the cathode using a vacuum thermal evaporation method.

[0071] In a preferred embodiment, the material forming the antireflective layer is MoO3, and the thickness of the antireflective layer is 33-37 nm, preferably 35 nm.

[0072] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, the raw materials used are all commercially available analytical grade products.

[0073] Unless otherwise specified, the following room temperature is 25±2 ℃.

[0074] Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) solution, purchased from Heraeus, model 4083.

[0075] Example 1: Synthesis of the non-fullerene macromolecular acceptor material 3QX-IC The non-fullerene macromolecular acceptor material 3QX-IC was prepared according to the following synthetic route: In the following synthetic route, -C8H 17 Indicates octyl; -C 11 H 23 Indicates undecyl; -C6H 13 It represents the foundation of self.

[0076]

[0077] (1) Synthesis of compound 2 Compound 1 (0.42 mmol) was added to a 50 mL three-necked flask and dissolved in ultra-dry THF (20.00 mL). Lithium aluminum hydride (8.36 mmol) was added at 0 °C, and the mixture was heated to 75 °C and refluxed under nitrogen for 6 hours. After cooling to room temperature, the reaction solution was slowly added dropwise to ice-saturated brine. Once the lithium aluminum hydride was completely quenched, the mixture was transferred to a separatory funnel. The organic phase was extracted with ethyl acetate, dried over anhydrous magnesium sulfate, and filtered off. The solvent in the organic phase was removed by vortexing to obtain compound 2.

[0078] (2) Synthesis of compound 4 Compound 2 (0.42 mmol) and compound 3 (0.08 mmol) obtained in the previous step were added to a 25 mL three-necked flask. Chlorobenzene (7.50 mL) and glacial acetic acid (7.50 mL) were added to dissolve them. The mixture was heated to 130 °C and refluxed under nitrogen for 12 hours. After cooling to room temperature, the reaction solution was slowly added to a saturated sodium bicarbonate solution. After complete quenching by acetic acid, the solution was transferred to a separatory funnel. The organic phase was extracted with dichloromethane, dried over anhydrous magnesium sulfate, and filtered off. Most of the solvent in the organic phase was removed by rotary evaporation. When a small amount of solvent (10 mL) remained, 900 mg of silica gel powder was added, and the mixture was then evaporated into a powder for column chromatography. A mixture of petroleum ether and dichloromethane (volume ratio 10:1) was used as the eluent. Column chromatography purification yielded compound 4, an orange oily liquid (66% yield).

[0079] 1 H NMR (400 MHz, CDCl3) δ (ppm): 7.96 (d, J = 8.2 Hz, 4H), 7.90 (d, J = 8.2Hz, 4H), 7.83 (d, J = 7.3 Hz, 4H), 7.36 (t, J = 7.6 Hz, 4H), 7.22 (t, J = 7.9 Hz,2H), 7.00 (s, 2H), 6.98 (s, 2H), 6.94 (s, 2H), 4.65 (d, J = 8.6 Hz, 12H), 2.84(dt, J = 15.3, 7.6 Hz, 8H), 2.76 (t, J= 7.5 Hz, 4H), 2.21 – 2.08 (m, 6H), 1.91 –1.81 (m, 8H), 1.81 – 1.74 (m, 4H), 1.46 – 0.87 (m, 240H), 0.80 – 0.62 (m,54H). 13 C NMR (101 MHz, CDCl3) δ (ppm): 137.47, 136.92, 130.30, 128.14, 123.50,38.58, 31.92, 31.88, 31.85, 31.80, 31.68, 31.63, 30.34, 29.72, 29.64, 29.54,29.49, 29.46, 29.41, 29.38, 29.31, 29.19, 29.14, 28.81, 25.46, 22.69, 22.65,22.60, 22.52, 22.47, 14.18, 14.12, 14.09, 14.05, 14.01. MS (MALDI-TOF, m / z)calcd for C246H360N12S12 [M] + : 3869.5247, found: 3869.5267. (3) Synthesis of compound 5 Add 2.00 mL of ultradry N,N-dimethylformamide to a 100 mL three-necked flask, and slowly add 0.60 mL of phosphorus oxychloride dropwise at 0 °C. Maintain the temperature at 0 °C and stir under nitrogen for 2 hours. Dissolve compound 4 (0.05 mmol) in 50.00 mL of ultradry 1,2-dichloroethane, then transfer the solution to a three-necked flask. Heat the solution to 80 °C and reflux under nitrogen for 12 hours. Cool to room temperature, and slowly add the reaction solution to 50 mL of saturated sodium carbonate solution. After complete quenching of phosphorus oxychloride, transfer the solution to a separatory funnel, extract the organic phase with dichloromethane, dry with anhydrous magnesium sulfate, and filter out the organic phase. When a small amount of solvent (10 mL) remains after rotary evaporation, 750 mg of silica gel powder is added, and the mixture is then evaporated into a powder solid for column chromatography. A mixture of petroleum ether and dichloromethane with a volume ratio of 6:1 is selected as the eluent. The mixture is purified by column chromatography to obtain compound 5 as an orange solid (yield of 84%).

[0080] 1 H NMR (400 MHz, Chloroform-d) δ(ppm): 10.15 (s, 2H), 10.14 (s, 2H),10.07 (s, 2H), 7.96 (d, J = 8.2 Hz, 4H), 7.91 (d, J = 8.3 Hz, 4H), 7.83 (d, J = 7.5Hz, 4H), 7.42 (t, J = 7.6 Hz, 4H), 7.31 (t, J = 7.4 Hz, 2H), 4.69 (d, J = 8.1 Hz,12H), 3.21 (q, J = 7.5 Hz, 8H), 3.11 (t, J = 7.6 Hz, 8H), 2.19 – 2.05 (m, 6H),1.98 – 1.86 (m, 8H), 1.86 – 1.76 (m, 4H), 1.50 – 0.87 (m, 240H), 0.80 – 0.62(m, 54H). 13 C NMR (101 MHz, CDCl3) δ(ppm): 181.85, 181.74, 150.35, 149.77,149.70, 147.01, 146.92, 144.32, 144.25, 139.88, 139.78, 139.74, 137.37,137.32, 137.28, 136.85, 136.76, 134.27, 134.18, 132.41, 132.32, 132.30,130.48, 130.35, 129.75, 129.68, 128.48, 128.30, 127.16, 127.12, 118.43, 118.37, 55.12, 38.89, 38.83, 31.88, 31.82, 31.76, 31.60, 31.55, 30.59, 30.53, 30.38, 30.29, 29.70, 29.62, 29.58, 29.56, 29.51, 29.46, 29.43, 29.38, 29.31, 29.26, 29.24, 29.19, 29.13, 28.09, 27.96, 25.45, 25.36, 22.67, 22.63, 22.60, 22.58, 22.51, 22.46, 14.16, 14.11, 14.05, 14.03, 13.99. MS (MALDI-TOF, m / z)calcd for C252H360N12O6S12 [M] + : 4037.4943, found: 4037.4991. (4) Synthesis of the non-fullerene macromolecular acceptor material 3QX-IC Compound 5 (0.04 mmol) and compound 6 (0.71 mmol) were added to a 100 mL three-necked flask, dissolved in 60.00 mL of chloroform, and then pyridine (6.00 mL) was added. The mixture was heated to 65 °C and refluxed under nitrogen for 12 hours. After cooling to room temperature, 90 v% of the solvent in the reaction solution was removed by rotary evaporation, and the remaining solution was precipitated in methanol and filtered to obtain a black solid. The solid was dissolved in 10 mL of dichloromethane, and 600 mg of silica gel powder was added. The mixture was then vortexed into a powder for column chromatography. A 3:1 (v / v) mixture of petroleum ether and dichloromethane was used as the eluent. The product was purified by column chromatography to obtain the non-fullerene acceptor material 3QX-IC as a black solid (yield 72%).

[0081] 1H NMR (400 MHz, Methylene Chloride-d2) δ (ppm): 9.22 (s, 2H), 9.15 (s,2H), 8.99 (s, 2H), 8.57 (dt, J = 30.3, 8.3 Hz, 6H), 8.10 – 7.84 (m, 12H), 7.72(dq, J = 24.6, 7.2 Hz, 6H), 7.60 – 7.40 (m, 6H), 5.07 – 4.73 (d, 12H), 3.32 (q, J = 5.4 Hz, 8H), 3.00 (t, J = 17.2 Hz, 4H), 2.37 – 2.20 (m, 6H), 2.05 – 1.90 (m,8H), 1.86 – 1.73 (m, 4H), 1.41 – 1.02 (m, 240H), 0.90 – 0.70 (m, 54H). MS(MALDI-TOF, m / z) calcd for C324H372F12N24O6S12 [M] + : 5310.6083, found:5310.5942. The present invention is exemplary in Figure 1 , Figure 2 , Figure 3 The 1H NMR spectra of compounds 4, 5, and the non-fullerene macromolecular acceptor material 3QX-IC are provided in the paper.

[0082] This invention uses a method similar to the preparation example described above to prepare other non-fullerene macromolecular acceptor materials used in this invention.

[0083] Test Example 1 (1) Thin films were prepared from the non-fullerene macromolecular acceptor material 3QX-IC, the classical non-fullerene acceptor material BTP-eC9, and the classical donor material D18 obtained in the above examples. The specific preparation methods are as follows: The test material was dissolved in chloroform to obtain a concentration of 10 mg / mL. -1 The test material solution was spin-coated onto a quartz plate at a speed of 3000 rpm for 30 s.

[0084] The prepared thin film was subjected to UV-Vis absorption testing; the specific test results are shown in [link to test results]. Figure 4 .Depend on Figure 4It can be seen that the D18 film has an absorption window in the 400-650 nm range, with its maximum absorption peak located at 579 nm. The BTP-eC9 film exhibits significant absorption in the 600-900 nm range, with its maximum absorption peak located at 826 nm. The 3QX-IC film shows a significant blue shift in its absorption spectrum compared to BTP-eC9, exhibiting significant absorption in the 300-550 nm and 600-850 nm ranges, with its maximum absorption peak located at 800 nm. D18, 3QX-IC, and BTP-eC9 exhibit clearly complementary absorption, which is beneficial for improving the short-circuit current of the ternary device. J SC ).

[0085] The electrochemical performance of the non-fullerene macromolecular acceptor material 3QX-IC, the classical non-fullerene acceptor material BTP-eC9, and the classical donor material D18 prepared in the above examples was tested. The specific testing method is as follows: The cyclic voltammetry (CV) curve of 3QX-IC was tested using a CHI760E A21731 electrochemical workstation, with a platinum disk as the working electrode, a platinum wire as the counter electrode, and Ag / AgCl as the reference electrode; tetrabutylammonium hexafluorophosphate was dissolved in ultra-dry acetonitrile to prepare a solution with a concentration of 0.10 mol / L. -1 The electrolyte solution was prepared by bubbling with nitrogen to remove oxygen. 3QX-IC was dissolved in a small amount of chloroform, and the solution was pipetted and dropped onto the platinum disk of the platinum disk electrode. After the chloroform evaporated, a uniform test film was formed. The test range was -0.8 V to 1.8 V. Finally, the CV curve of the ferrocene standard was measured. Specific results are as follows: Figure 5 , Figure 6 As shown.

[0086] Figure 5 The CV curve of 3NQX-IC as determined by electrochemical cyclic voltammetry (CV).

[0087] Figure 6 The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels of D18, 3QX-IC, and BTP-eC9 are shown to be -5.51 / -2.77 eV, -5.48 / -3.92 eV, and -5.64 / -4.01 eV, respectively. The three devices exhibit a cascaded energy level arrangement, which is beneficial for charge transport in the ternary device, thereby improving its performance. J SC and fill factor (FF).

[0088] Figure 7The optimal geometry of 3QX-IC, a non-fullerene macromolecular acceptor material, was calculated using DFT theory. 3QX-IC features three A-DA'DA type small molecule acceptors tightly and rigidly connected along the central A' unit direction via a benzene ring linker. The dihedral angle between the plane containing the benzene ring and the plane containing the quinoxaline group is 151.3°, indicating that 3QX-IC exhibits a distinct three-dimensional structure. This helps suppress intermolecular aggregation and is beneficial for achieving high performance in binary and ternary devices. V OC On one side of 3QX-IC, two A-DA'DA type small molecule acceptors are distributed nearly vertically, exhibiting a unique bilayer structure that can form intramolecular charge transfer channels; the other side exhibits a near-planar configuration, which is conducive to achieving ordered molecular stacking in the direction of the terminal groups; both of these are beneficial to improving... J SC And FF.

[0089] Test Example 2: Fabrication and Performance Testing of Organic Solar Cells (1) Solution preparation A. Preparation of the active layer solution: When fabricating the D18:3QX-IC binary device, the active layer solution is prepared as follows: First, prepare 1 mL of DIB-chloroform solution, with a DIB concentration of 5.00 mg / mL. -1 Then, the donor material D18 and the acceptor material 3QX-IC were dissolved in the above DIB-chloroform solution at a mass ratio of 1:1.2, resulting in a total concentration of 11.00 mg / mL for both the donor and acceptor materials. -1 Stir at 75 °C for 6 hours to ensure complete dissolution.

[0090] When fabricating the D18:BTP-eC9 binary reference device, the active layer solution was prepared as follows: First, a 1 mL solution of chloroform containing DIB was prepared, with a DIB concentration of 5.00 mg / mL. -1 Then, the donor material D18 and the acceptor material BTP-eC9 were dissolved in the above DIB-chloroform solution at a mass ratio of 1:1.2, resulting in a total concentration of 11.00 mg / mL for both the donor and acceptor materials. -1 Stir at 75 °C for 6 hours to ensure complete dissolution.

[0091] When preparing the D18:BTP-eC9:3QX-IC ternary device, the active layer solution is prepared as follows: First, prepare 1 mL of DIB-chloroform solution, with a DIB concentration of 5.00 mg / mL. -1Then, donor material D18, acceptor BTP-eC9, and third component 3QX-IC were dissolved in the above DIB-chloroform solution at a mass ratio of 1:1.08:0.12, resulting in a total concentration of 11.00 mg / mL for the donor, acceptor, and third component. -1 Stir at 75 °C for 6 hours to ensure complete dissolution.

[0092] B. Preparation of electron transport layer solution: Dissolve PDIN in methanol to a concentration of 2.0 mg / mL. -1 Then add 0.3% by volume of acetic acid.

[0093] (2) Device fabrication Anodizing: The patterned ITO glass substrate was ultrasonically cleaned for 15 minutes each with detergent, deionized water, acetone and isopropanol, and then dried with nitrogen gas. After that, it was treated with ultraviolet-ozone for 15 minutes.

[0094] (a) Spin-coating hole transport layer: PEDOT:PSS solution was spin-coated on the ITO surface at 3500 rpm for 30 seconds, and then annealed at 150°C for 15 minutes to form a 5 nm hole transport layer.

[0095] (b) Spin-coating of active layer: In a glove box, spin-coat the active layer solution onto the hole transport layer at 2500 rpm for 30 seconds, followed by annealing at 100 °C for 10 minutes to form a film of about 100 nm thick.

[0096] (c) Spin-coating electron transport layer: PDIN solution was spin-coated onto the formed active layer at a speed of 3500 rpm for 30 seconds to form a 5 nm electron transport layer.

[0097] (d) Evaporation of cathode: The product obtained in step (c) is transferred to a vacuum evaporation chamber and deposited at <5×10⁻⁶. -4 A 100 nm thick silver electrode was deposited by vapor deposition under a vacuum of Pa.

[0098] (3) Performance testing The SS-X AAA-grade solar simulator was used to perform current-voltage (current-voltage) tests on the D18:3QX-IC binary device, the D18:BTP-eC9 binary reference device, and the D18:BTP-eC9:3QX-IC ternary device. J - V The curve test was conducted using an AM 1.5G light source with an irradiance of 100 mW / cm². -2 The test results are as follows Figure 8 As shown. Among them, The performance parameters of the D18:3QX-IC binary component are as follows: V OC = 0.959 V,J SC = 19.47 mA cm -2 FF = 67.81%, PCE = 12.66%. The D18:3QX-IC binary device exhibits a high voltage rating exceeding 0.95 V. V OC This demonstrates that 3QX-IC possesses low energy loss characteristics. This allows 3QX-IC to effectively improve the performance of ternary devices when used as the third component of the active layer. V OC This will improve the PCE of the ternary components.

[0099] The performance parameters of the D18:BTP-eC9 binary reference device are as follows: V OC = 0.862 V, J SC = 28.17 mA cm -2 , FF= 75.84%, PCE = 18.41%.

[0100] The performance parameters of the D18:BTP-eC9:3QX-IC three-element component are as follows: V OC = 0.883 V, J SC = 28.31 mA cm -2 FF = 76.06%, PCE = 19.01%. This indicates that 3QX-IC, as the third component of the active layer, can effectively improve the performance of ternary devices. V OC , J SC Key parameters such as FF significantly enhance the PCE of ternary components.

[0101] (4) External quantum efficiency test The external quantum efficiency (EQE) spectroscopic tests of the aforementioned binary, binary reference, and ternary devices were performed using the Solar Cell Scan100 external quantum efficiency testing system. The test results are as follows: Figure 9 As shown.

[0102] The D18:3QX-IC binary device, D18:BTP-eC9 binary reference device, and D18:BTP-eC9:3QX-IC ternary device were obtained by integrating the EQE spectrum. J SC cal The values ​​were 18.54 mA cm. -2 26.95 mA cm -2 and 27.05mA cm -2 ,andJ - V Test results obtained J SC The deviations were all within 5%, which is within the acceptable error range.

[0103] D18: The EQE response value of the 3QX-IC binary component is relatively low, which is due to the binary component's... J SC The reason for the relatively low FF is that the D18:BTP-eC9:3QX-IC ternary device exhibits a stronger EQE response than the D18:BTP-eC9 binary reference device in both the 350-470 nm and 780-890 nm ranges. This corresponds to the ternary device... J SC And the improvement of FF.

[0104] Example 3: Fabrication and Performance Testing of Semi-Transparent Organic Solar Cells (1) Solution preparation A. Preparation of the active layer solution: When preparing the D18:BTP-eC9 binary reference semi-transparent device, the active layer solution was prepared as follows: First, 1 mL of DIB-chloroform solution was prepared, with a DIB concentration of 5.00 mg / mL. -1 Then, the donor material PM6 and the acceptor material BTP-eC9 were dissolved in the above DIB-chloroform solution at a mass ratio of 1:2, resulting in a total concentration of 15.00 mg / mL for both the donor and acceptor materials. -1 Stir at 75 °C for 6 hours to ensure complete dissolution.

[0105] When fabricating the D18:BTP-eC9:3QX-IC ternary semi-transparent device, the active layer solution is prepared as follows: First, prepare 1 mL of DIB-chloroform solution, with a DIB concentration of 5.00 mg / mL. -1 Then, donor material D18, acceptor BTP-eC9, and third component 3QX-IC were dissolved in the above DIB-chloroform solution at a mass ratio of 1:1.8:0.2, resulting in a total concentration of 15.00 mg / mL for the donor, acceptor, and third component. -1 Stir at 75 °C for 6 hours to ensure complete dissolution.

[0106] B. Preparation of electron transport layer solution: Dissolve PDIN in methanol to a concentration of 2.0 mg / mL. -1 Add 0.3% by volume of acetic acid.

[0107] (2) Device fabrication Device structure such as Figure 10As shown; the specific preparation method is as follows: Anodizing: The patterned ITO glass substrate was ultrasonically cleaned for 15 minutes each with detergent, deionized water, acetone and isopropanol, and then dried with nitrogen gas. After that, it was treated with ultraviolet-ozone for 15 minutes.

[0108] (a) Spin-coating hole transport layer: PEDOT:PSS solution was spin-coated on the ITO surface at 3500 rpm for 30 seconds, and then annealed at 150°C for 15 minutes to form a 30 nm hole transport layer.

[0109] (b) Spin-coating of the active layer: In a glove box, the active layer solution was spin-coated onto the hole transport layer at 3000 rpm for 30 seconds. It was then annealed at 100 °C for 10 minutes to form a 100 nm thick film.

[0110] (c) Spin-coating electron transport layer: PDIN solution was spin-coated onto the formed active layer at a speed of 3500 rpm for 30 seconds to form a 5 nm electron transport layer.

[0111] (d) Evaporation of cathode: The product obtained in step (c) is transferred to a vacuum evaporation chamber and deposited at <5×10⁻⁶. -4 Under a vacuum of Pa, a 3 nm thick copper electrode is first deposited by vapor deposition, followed by a 5 nm thick silver electrode.

[0112] Anti-reflective layer: 35 nm MoO3 is deposited on the surface of the silver electrode as an anti-reflective layer.

[0113] (3) Photoelectric performance testing The SS-X AAA-grade solar simulator was used to perform current-voltage (current-voltage) analysis on the D18:BTP-eC9 binary reference semi-transparent device and the D18:BTP-eC9:3QX-IC ternary semi-transparent device. J - V The curve test was conducted using an AM 1.5G light source with an irradiance of 100 mW / cm². -2 The test results are as follows Figure 11 As shown. Among them, The performance parameters of the D18:BTP-eC9 binary reference semi-transparent device are as follows: V OC = 0.855 V, J SC = 17.92 mAcm -2 , FF = 70.71%, PCE = 10.83%.

[0114] The performance parameters of the D18:BTP-eC9:3QX-IC ternary semi-transparent device are as follows: V OC= 0.887 V, J SC = 18.18mA cm -2 FF = 72.51%, PCE = 11.47%. This indicates that 3QX-IC, as the third component of the active layer, can effectively improve the performance of ternary semi-transparent devices. V OC , J SC Key parameters such as FF are improved, significantly enhancing the PCE of ternary semi-transparent devices.

[0115] (4) Optical performance testing The transmission spectra of binary reference materials and ternary semi-transparent devices were measured using a UV-3600i ultraviolet-visible spectrophotometer. The test results are as follows: Figure 12 As shown. According to Figure 12 Based on the spectrum, the average visible light transmittance (AVT) of the D18:BTP-eC9 binary reference semi-transparent device was calculated to be 28.07%, and the AVT of the D18:BTP-eC9:3QX-IC ternary semi-transparent device was 32.85%. This indicates that 3QX-IC, as the third component of the active layer, can effectively improve the AVT of the ternary semi-transparent device.

[0116] Light utilization efficiency (LUE) is the primary parameter for evaluating semi-transparent devices, defined as the product of PCE and AVT. Thanks to the dual improvement in PCE and AVT, the D18:BTP-eC9:3QX-IC ternary semi-transparent device achieves an LUE of 3.77%, far exceeding the 3.04% LUE of the D18:BTP-eC9 binary reference semi-transparent device.

[0117] Color reproduction index (CRI) is another important parameter for evaluating translucent devices. It is defined as a measure of how well an object matches the color when illuminated by a standard light source (sunlight), with a maximum value of 100. Figure 13 The images show the CRI of the real-world image, the D18:BTP-eC9 binary reference semi-transparent device, and the D18:BTP-eC9:3QX-IC ternary semi-transparent device, which are 100, 84.93, and 93.41, respectively. This indicates that 3QX-IC, as the third component of the active layer, can effectively improve the CRI of the ternary semi-transparent device.

[0118] Figure 14The CIE coordinates of white light, the D18:BTP-eC9 binary reference semi-transparent device, and the D18:BTP-eC9:3QX-IC ternary semi-transparent device are shown, which are (0.330, 0.330), (0.319, 0.309), and (0.327, 0.327), respectively. The CIE coordinates of the D18:BTP-eC9:3QX-IC ternary semi-transparent device are closer to those of white light than those of the D18:BTP-eC9 binary reference semi-transparent device. This also proves that 3QX-IC, as the third component of the active layer, can effectively improve the color reproduction capability of the ternary semi-transparent device.

[0119] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A non-fullerene macromolecular acceptor material based on quinoxaline structure modification, characterized in that, The non-fullerene macromolecular acceptor material has the structure shown in formula (I): Equation (I); Formula (II); In formula (I), R1, R2, R3 and R4 are each independently selected from C1-C30 alkyl groups; A1 and A2 are each independently groups represented by formula (II); in formula (II), R5 and R6 together cyclize to form a benzene ring selected from substituted or unsubstituted, a naphthalene ring selected from substituted or unsubstituted, or a thiophene ring selected from substituted or unsubstituted. Furthermore, the substituents optionally present on R5 and R6 are each independently selected from at least one of halogens, C1-C3 alkyl groups, and C1-C3 alkoxy groups.

2. The non-fullerene macromolecular acceptor material according to claim 1, characterized in that, In formula (I), R1, R2, R3 and R4 are each independently selected from C6-C30 alkyl groups; Preferably, R1, R2, R3, and R4 are each independently selected from one of the following groups: 。 3. The non-fullerene macromolecular acceptor material according to claim 1 or 2, characterized in that, In formula (I), A1 and A2 are each independently selected from one of the following groups: 、 、 、 ; Optionally, A1 and A2 may further contain at least one substituent selected from halogens, C1-C3 alkyl groups, and C1-C3 alkoxy groups.

4. The non-fullerene macromolecular acceptor material according to claim 3, characterized in that, In formula (I), A1 and A2 are each independently selected from one of the following groups: 。 5. The non-fullerene macromolecular acceptor material according to any one of claims 1-4, characterized in that, The non-fullerene macromolecular acceptor material is selected from one of the following structures: 。 6. A method for preparing the A-DA'DA type non-fullerene macromolecular acceptor material based on quinoxaline structure modification as described in any one of claims 1-5, characterized in that, The method includes the following steps: under the protection of an inert atmosphere, (1) In the presence of a solvent, compound A and compound B undergo a first condensation reaction to obtain compound C; (2) In the presence of a solvent, compound C is subjected to a formylation reaction with N,N-dimethylformamide (DMF) and phosphorus oxychloride to obtain compound D; (3) In the presence of solvent and pyridine, compound D and compound E are subjected to a second condensation reaction to obtain the non-fullerene macromolecular acceptor material shown in formula (I); Compound A: Compound B: ; Compound E: ;Formula (I): ; In formula (I), compound A, compound B, and compound E, the definitions of R1, R2, R3, R4, R5, R6, A1, and A2 correspond to the definitions in any one of claims 1-5.

7. The method according to claim 6, characterized in that, In step (1), the molar ratio of compound A to compound B is 3-6:1; In step (2), the amount of N,N-dimethylformamide used is 35-45 mL relative to 1 mmol of compound C, and the amount of phosphorus oxychloride used is 11-13 mL; In step (3), the molar ratio of compound D to compound E is 1:16-18.

8. An organic solar cell, characterized in that, The organic solar cell includes an active layer containing a donor material, an acceptor material, and a third component; The third component is the A-DA'DA type non-fullerene macromolecular acceptor material as described in any one of claims 1-5.

9. The organic solar cell according to claim 8, characterized in that, The organic solar cell comprises an anode, a hole transport layer, an active layer, an electron transport layer, and a cathode, which are stacked sequentially.

10. The organic solar cell according to claim 8 or 9, characterized in that, The mass ratio of the donor material to the acceptor material is 1:1-1.5; Preferably, the donor material is D18; the acceptor material is BTP-eC9; Preferably, the third component accounts for 5-30 wt% of the total mass of the receptor material and the third component.